2020
DOI: 10.1007/s11548-020-02148-5
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning-based anatomical site classification for upper gastrointestinal endoscopy

Abstract: Purpose Upper gastrointestinal (GI) endoscopic image documentation has provided an efficient, low-cost solution to address quality control for endoscopic reporting. The problem is, however, challenging for computer-assisted techniques, because different sites have similar appearances. Additionally, across different patients, site appearance variation may be large and inconsistent. Therefore, according to the British and modified Japanese guidelines, we propose a set of oesophagogastroduodenoscopy (EGD) images … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 24 publications
(34 reference statements)
0
11
0
Order By: Relevance
“…In laparoscopic cholecystectomy, automated video retrieval can help in assessing whether a critical view of safety was achieved [36], with potential risk reduction and a safer removal of the gallbladder. Additionally, the detection and classification of anatomy enables Visc Med 2020;36:456-462 DOI: 10.1159/000511934 the automatic generation of standardized procedure reports for quality control assessment and clinical training [37].…”
Section: Anatomy Detectionmentioning
confidence: 99%
“…In laparoscopic cholecystectomy, automated video retrieval can help in assessing whether a critical view of safety was achieved [36], with potential risk reduction and a safer removal of the gallbladder. Additionally, the detection and classification of anatomy enables Visc Med 2020;36:456-462 DOI: 10.1159/000511934 the automatic generation of standardized procedure reports for quality control assessment and clinical training [37].…”
Section: Anatomy Detectionmentioning
confidence: 99%
“…Utilising AI to automatically generate endoscopy reports would be a welcome solution. It has already been demonstrated that AI models can automatically identify key anatomical landmarks in luminal endoscopy, record withdrawal time, quality of bowel preparation and recognise tools [34][35][36]. Furthermore, computer vision applications can now identify phases of intervention and actions, which will likely translate to automated generation of performance measures for endoscopy quality.…”
Section: Automated Reporting/quality Assessmentmentioning
confidence: 99%
“…Currently, image-based deep learning methods determine the endoscope's position from the classification of endoscopic images using inherent visual features [6,7]. When image labeling is provided [14], a topological scene association can be formed.…”
Section: Related Workmentioning
confidence: 99%
“…A primary benefit of this step is the simplified view of the anatomical environment since only semantic image content is addressed in the labeling of training data. Similar to [6], our approach uses the description of anatomical landmarks for the labeling of image data to simplify the task of predicting navigation steps to an association of subsequent scenes observed with content of landmarks. However, rather than focusing on spatial properties, we want to use the inherent temporal information between labeled images to extract a representation of states between images that show particular endoscope positions.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation